2016
DOI: 10.1016/j.jbi.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of gene ranking methods in phenotype prediction

Abstract: We have shown that noise in expression data and class assignment partially falsifies the sets of discriminatory probes in phenotype prediction problems. FR and SAM better exploit the principle of parsimony and are able to find subsets with less number of high discriminatory genes. The predictive accuracy and the precision are two different metrics to select the important genes, since in the presence of noise the most predictive genes do not completely coincide with those that are related to the phenotype. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…These gene-ranking methods and particularly Fisher's ratio turned to be very robust against different kind of noise [24]. Genes with the highest discriminatory power as described by these methods are expected to be involved in the genesis of the CLL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These gene-ranking methods and particularly Fisher's ratio turned to be very robust against different kind of noise [24]. Genes with the highest discriminatory power as described by these methods are expected to be involved in the genesis of the CLL.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology tries to determine the shortest lists of most discriminatory genes that predict the NOP16 mutation and is described by Fernández-Martínez et al [20] and De Andrés-Galiana et al [22][23][24]. This classification problem is naturally unbalanced due to the low number of patients that show the NOP16 mutation, and the classifier has to take this feature into account.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another attempt to tackle noise in microarray reading, authors used microarray synthetic modeling to compare different gene ranking methods (fold change, Fisher's ratio, percentile distance, and entropy) and significance analysis of microarrays. They used the aforementioned ALS and IBM datasets and concluded that the Fisher ratio was the most precise method with the highest discriminatory power [59].…”
Section: Disease Mechanismsmentioning
confidence: 99%
“…Besides, due to the high underdetermined character of the phenotype prediction problems, their associated uncertainty space has a very high dimension, and the characterization of the involved biological pathways is very ambiguous because there exist many equivalent genetic networks that predict the phenotype with similar accuracies. [75][76][77] The important working hypothesis is that by sampling the uncertainty space of the phenotype prediction problems, we are able to understand the altered genetic pathways of the disease in order to use this knowledge in precision medicine for diagnosis, prognosis, and treatment optimization. Different interesting methods were proposed by Cernea et al 8 and successfully applied in the analysis of Triple Negative Breast Cancer metastasis, comparing the results obtained with Bayesian networks.…”
Section: Ai Genomics and The Phenotype Prediction Problemmentioning
confidence: 99%